New species and new records of the subgenus Galumnella (Galumnella) (Acari: Oribatida: Galumnellidae) from China - Liang, Wenqin; Yang, Maofa; Ren, Guoru; Zheng, Qianfen (Zootaxa, 2019)
Two new species of oribatid mites of the subgenus Galumnella (Galumnella) (Acari: Oribatida: Galumnellidae) are described from soil and litter of forest zones of China. Galumnella (G.) nonporosa sp. nov. differs from Galumnella (G.) nipponica by the falciform bothridial setae and obvious reticulate pattern in the anogenital region. Galumnella (G.) sidorchukae sp. nov. differs from Galumnella (G.) cellularis by the laciniate bothridial setae and by the absence of postanal porose area. Morphological additions to the description of Galumnella (G.) parageographica are presented based on Chinese specimens, which is recorded in China for the first time.